2022
DOI: 10.1155/2022/9991523
|View full text |Cite|
|
Sign up to set email alerts
|

Injury Prevention Effect of MRI Imaging Technology in Physical Education and Sports Training

Abstract: In order to solve the problem of observing and analyzing the clinical value of MRI diagnosis in patients with knee sports injury and guiding clinical targeted treatment, the author proposed a sports injury prevention method in sports training teaching based on MRI image observation. This method retrospectively analyzed the imaging data of 101 patients with knee joint MRI examination due to osteoarthritis, sports injury and synovitis in joint surgery, and arthroscopic exclusion of true meniscus tear, MR multise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%